Preparation of long afterglow luminescent road marking coatings and its applicability simulation - Guojun Li; Ning Li; Yan Zhang; Jie Han; Tengfei Yao; Xiaowei Feng (PLoS ONE, 2025)
Traffic markings have inadequate nighttime visibility for safe driving. To address this and reduce nighttime accidents, we researched and developed long afterglow luminescent coatings, including performance and simulation studies. By varying the dosage of luminescent powder, glass powder, and titanium dioxide, nine groups of coatings were fabricated via blending. Their luminescence and chromaticity properties were investigated. Using CW-VIKOR comprehensive evaluation, the optimal formulation was selected. This optimal coating was further analyzed using Twinmotion and DIALux simulations, assessing marking visibility and tunnel illumination effects with the coatings.Results revealed that increased luminescent powder dosage enhanced luminescence performance. The optimal formulation (30% luminescent powder, 8% glass powder, 4% titanium dioxide) achieved the best luminescence performance and colorimetric characteristics, sustaining light emission for 9 hours with good road performance. Twinmotion simulations demonstrated better nighttime visibility at different brightness levels. DIALux simulations showed a 22.3% increase in average tunnel brightness after coating deployment, significantly improving lighting effects.